Examining the Role of Responsibility and Belief in a Just World in the Relationship between Parental Rejection and Adolescents’ Gratitude - Jingwen Xing; Xiaofeng Xu; Xingchao Wang (Behavioral Sciences, 2023)
Parenting is an important factor affecting teenagers’ gratitude, but few studies have deeply examined the impact of specific parenting behavior on teenagers’ gratitude. In this study, 357 high school students were tested by questionnaires to examine the mechanism of parental rejection on adolescents’ gratitude. Results showed that (1) parental rejection significantly and negatively predicted adolescents’ gratitude, and that (2) after controlling for gender and age, parental rejection would indirectly impact adolescents’ gratitude through responsibility and belief in a just world, respectively. These results suggested that responsibility and belief in a just world were important factors in reducing the negative effect of parental rejection on teenagers’ gratitude.